Efek Kapasitas Sumber Daya Manusia Dan Komitmen Organisasi Terhadap Nilai Informasi Pelaporan Keuangan - Suharlina, Suharlina (Jurnal Unicorn ADPERTISI, 2023)
The aims of this study are as follows: To find out and test the effect of human resource capacity on the value of financial reporting information at the City Government of Makassar; To find out and deal with the effect of organizational depreciation on the value of financial reporting information at the City Government of Makassar. This study uses a quantitative approach, namely a method based on the philosophy of positivism, which is used to study a certain population or sample, collect data with research tools, analyze data statistically, with the aim of testing confirmed hypotheses. The population of this study is 57 OPD in Makassar City. The method used by researchers in selecting research samples was purposive sampling so that the sample in this study consisted of the head of finance and four financial officials in each agency, so the total sample was 45 people. The analysis used is multiple linear regression analysis. The results of this study is that human resource capacity has no significant effect on the value of financial reporting information. Then, the hand of the organization has a significant effect on the value of financial reporting information.